AKUISISI DATA MENGGUNAKAN LABVIEW DENGAN ARDUINO SEBAGAI PERANGKAT KERAS BERBIAYA RENDAH - Bagenda, Dadan Nurdin; Rudati, Paula Santi (Vocational School Diponegoro University, 2020)
Industrial and academic laboratories cannot be separated from the use of DAQ, most of industrial automation generally requires massive amounts of DAQ and high speed. DAQ LabView software provides various facilities so that projects can be faster. Honestly, the price of hardware for DAQ is relatively expensive, luckily LabView give the opportunity to support ability many hardware including Arduino Board. Using the LINX library from Makerhub are free, so that the DAQ Practicum as industry standard can be done by affordable prices. The results without Linx, the average travel time for serial deliveries is 5.98 us/byte at 2Mbps. With Linx,